A Study of Marx’s View of Time and Its Contemporary Value - Quan Cheng (International Journal of Social Sciences and Public Administration, 2026)
The problem of time is an age-old enigma, and research interest in it remains undiminished in physics and philosophy to this day. Yet more than a hundred years ago Marx had already unveiled its mystery: time is praxis-the active existence of the human being, the measure of human life, and the space for human development. “Corporealized” sensuous time constructs the human cognitive world-phenomenal nature; labor time as “living time” constructs the human existential world-actual society; and historical time realizes the human world of perpetuation-history. Marx first transposes praxis into the human being, then proceeds from real human individuals and, from a two-way open historical horizon, explores the meaning of time in social history, thereby transcending the conceptions of time in traditional philosophy and natural science. Through a deep disclosure of Marx’s view of time, this paper aims to elucidate its essential content and to clarify the consistency and systematicity of his thought on time.